Enhancing Students’ Achievement in Geometry Using Laboratory-Based Instructional Method - Ajai, John Tyavbee; Titilayo , Ogungbile; Jimin, Nguuma (International Journal of Research in STEM Education, 2024)
This study investigated the effect of laboratory-based instructional methods on students' achievement in geometry within the educational context of Jalingo Metropolis, Taraba State, Nigeria. Recognising the potential of hands-on, experiential learning approaches in mathematics education, particularly in geometry, this research explored the effectiveness of laboratory-based instruction in enhancing student performance. Guided by three research questions and hypotheses, the quasi-experimental research design was employed on a sample of 160 Upper Basic II students, through pre-and post-test assessments. The Geometry Achievement Test (GAT) with a reliability index of 0.91 for the GAT, determined using the K-R20 method, was used for data collection. The mean and standard deviation statistics were employed to answer the three research questions, while covariance (ANCOVA) analysis was employed to test all hypotheses at a significance level of 0.05. The study found a significant improvement in geometry achievement among students exposed to the laboratory-based method, with 56% of the achievement score variance attributed to this method. Additionally, it identifies a noteworthy difference in achievement scores between male and female students taught geometry using the laboratory-based approach, with a significant interaction effect observed between the teaching method and gender. These findings emphasise the potential of incorporating laboratory-based instructional methods in mathematics education to enhance student achievement and promote a deeper understanding of geometric concepts. Overall, the study contributes valuable insights to the discourse on innovative pedagogical practices in mathematics instruction, offering guidance for educators and policymakers aiming to improve mathematics education in similar contexts.